Effect of poultry litter on silage maize (Zea mays L.) production and nutrient uptake - Hirzel, J.; Matus, I.; Novoa, F.; Walter, I.; Walter, I. (Spanish Journal of Agricultural Research, 2007)
In Chile, the availability of poultry manure has recently increased as a result of expanding poultry production. The application of this organic waste on agricultural land is desirable since it not only helps recycle nutrients but also solves the problem of its disposal. A two year field study was undertaken to compare the effects of poultry litter (PL) and traditional mineral fertilizer on the growth of silage maize (Zea mays L.). The effects of adding mean annual PL rates of 10, 15 and 20 Mg haE-1, with and without mineral fertilizer, were compared with those of two rates of conventional mineral fertilizer and a control treatment (no fertilizer). Crop yield showed a positive response to the fertilized treatments and fluctuated between 26.30 and 37.13 Mg haE-1; values for the controls ranged between 17.12 and 23.80 Mg haE-1. The yield averages obtained with the PL treatments were 13.85 and 9.05 Mg haE-1 higher than the controls in the first and second year respectively. Nutrient uptake was similar with the PL and conventional fertilizer treatments. The mean of apparent efficiency of N recovery (AENR) for the PL treatments was higher than that of conventional fertilizer treatments, suggesting PL to be an appropriate N supply that suffers only small N losses. The highest AENR was obtained with the lowest PL dose, indicating this to be the most appropriate rate. In conclusion, PL is an efficient alternative to conventional mineral fertilizers for silage maize production.